Neural crest origin of perivascular mesenchyme in the adult thymus. - Stolt, Claus; Wegner, Michael; et al. (Journal of Immunology, 2008)
The endodermal epithelial thymus anlage develops in tight association with neural crest (NC)-derived mesenchyme. This epithelial-NC interaction is crucial for thymus development, but it is not known how NC supports thymus development or whether NC cells or their progeny make any significant contribution to the adult thymus. By nude mouse blastocyst complementation and by cell surface phenotype, we could previously separate thymus stroma into Foxn1-dependent epithelial cells and a Foxn1-independent mesenchymal cell population. These mesenchymal cells expressed vascular endothelial growth factor-A, and contributed to thymus vascularization. These data suggested a physical or functional association with thymic blood vessels, but the origin, location in the thymus, and function of these stromal cells remained unknown. Using a transgenic mouse expressing Cre recombinase in premigratory NC (Sox10-Cre), we have now fate-mapped the majority of these adult mesenchymal cells to a NC origin. NC-derived cells represent tightly vessel-associated pericytes that are sandwiched between endothelium and epithelium along the entire thymus vasculature. The ontogenetic, phenotypic, and positional definition of this distinct perivascular mesenchymal compartment provides a cellular basis for the role of NC in thymus development and possibly maintenance, and might be useful to address properties of the endothelial-epithelial barrier in the adult thymus. Copyright © 2008 by The American Association of Immunologists, Inc.
UnivIS-Import:2015-03-09:Pub.2008.med.IB.LPCIPDBI.neural